PENGARUH KEBIJAKAN FOREIGN DIRECT INVESTMENT (FDI) TERHADAP BISNIS RITEL DI INDONESIA - Siallagan, Asrina Br; Waluyo, Tri Joko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research analyzes the effect of FDI on retail industry in Indonesia. Retail industry in Indonesia has grow rapidly. Ritel industry expansion in Indonesia is the effect of the government policy that pros with ritel liberalism which manifasted with put the ritel bussines out from the negative list towards foreign investment. As a result, the bussines executant constanly peep out from domestic nor trans-border. FDI (Foreign Direct Investment) is believed to be one important source of financing fordeveloping countries including Indonesia. The presence of FDI is expected to provide asubstantial contribution to development through the transfer of assets, technology andmanagerial skills to improve an economic growth. The expansion of ritel industry can not be separated from the impact of globalizationThe theme of globalization and economic liberalization of the market mechanism has to unite and accelerate economic activity around the world by reducing the various costs and tarrifs become barriers to international trade. Along with that, capital and foreign investment, including from the retail business sector, to move quickly to find a place that is considered to be profitable as possible, and one where it is the state of Indonesia.This research use ecomic liberalization perspective. Economic liberalism can understanded as the movement to the free market system in globalization era that have purpose to omit the protectionism policy.Key words : Foreign Direct Investment (FDI), retail business, globalization, Indonesia.